Occupational Exposure to Blood and Body Fluids - M Bahadori (The International Journal of Occupational and Environmental Medicine, 2010)
Occupational exposure to blood and body fluids is an important hazard for health care workers, which places them at a high risk for blood-borne infections including hepatitis B virus, hepatitis C virus and human immunodeficiency virus and results in psychological and emotional stresses. Several preventive measures have been proposed including pre-exposure (e.g., education, use of standard precautions, use of needle protective devices, and vaccination) and post-exposure (e.g., post-exposure prophylaxis and early detection of disease) prevention. In this article, the importance of occupational exposure to blood and body fluids and the basic concepts of exposure prevention and management are reviewed.